(untitled) (Reflection and Critique Law Magazine, 2024)
This paper aims to analyze the role of the Supreme Court in consolidating Brazilian federalism, especially after the Covid-19 pandemic. The research adopts the deductive method and the documentary research technique. In conclusion, it is possible to identify a jurisprudential turn in the Supreme Federal Court in favor of federalism and the system of checks and balances, considering the hegemonic attempt of the Union to determine measures to fight coronavirus. In the context of the health emergency, the Court reaffirmed the constitutionally guaranteed autonomy of federal entities. However, it is not possible to say that the change will be permanent, being necessary to wait for new decisions in a normal scenario.